2021
DOI: 10.3390/ijerph18179415
|View full text |Cite
|
Sign up to set email alerts
|

Emotional Control among Nurses against Work Conditions and the Support Received during the SARS-CoV-2 Pandemic

Abstract: Introduction. Working in the state of a pandemic is a huge mental load for the medical environment. Aim. Evaluation of emotional control among nurses against work conditions and the support received during the SARS-CoV-2 pandemic. Material and methods. The research was performed among nurses (n = 577) working during the pandemic caused by the SARS-CoV-2 virus in infectious (n = 201) and non-infectious (n = 376) wards in 11 Polish hospitals. To evaluate work conditions, the questionnaire prepared by the authors… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(15 citation statements)
references
References 29 publications
0
15
0
Order By: Relevance
“…Its findings showed that nurses adopted suppression mechanisms as a way of coping with negative emotions caused by work in pandemic conditions. These are alarming findings as suppressing emotional expression, especially during the common pandemic threat, intensifies them or brings about long-term effects, such as emotional tension with harmful consequences to one’s health [ 82 ]. Unexpressed emotions can contribute to developing neurotic disorders and psychosomatic diseases.…”
Section: Discussionmentioning
confidence: 99%
“…Its findings showed that nurses adopted suppression mechanisms as a way of coping with negative emotions caused by work in pandemic conditions. These are alarming findings as suppressing emotional expression, especially during the common pandemic threat, intensifies them or brings about long-term effects, such as emotional tension with harmful consequences to one’s health [ 82 ]. Unexpressed emotions can contribute to developing neurotic disorders and psychosomatic diseases.…”
Section: Discussionmentioning
confidence: 99%
“…The research was carried out between December 2020 and March 2021 on a group of nurses (male/female) working in the southern regions of Poland. It was a part of a larger project seeking to valorize the roles of nurses during the SARS-CoV-2 pandemic, performed by Malopolska District Chamber of Nurses and Midwives in Krakow (Polish: MOIPiP) [ 20 ]. The trial was goal-oriented.…”
Section: Methodsmentioning
confidence: 99%
“…Inhibiting the expression of these emotions leads to their intensifcation, or in the case of their maintenance, to emotional tension. According to experts, expressing negative emotions is benefcial and is recommended in psychotherapy [14].…”
Section: Introductionmentioning
confidence: 99%